PENERAPAN METODE PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR SISWA DI KELAS IV SD SWASTA PAB 19 BANDAR KLIPPA - Masdalia Rambe; Zon Saroha Ritonga (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
This thesis aims to see an increase in student learning outcomes through the Problem Solving method. This thesis examines the unequal distribution of learning outcomes for private students at PAB 19 Bandar Klippa which is known from the results of observations. Learning that is only teacher-centered results in students not being active in class, and teachers being less innovative in developing learning regarding the use of media or learning methods. The method used is Classroom Action Research through two cycles consisting of planning, implementation, observation and reflection activities. The subjects of this research were fourth grade students at PAB 19 Bandar Klippa Private Elementary School, totaling 42 students. The instruments in this research used observation and tests. The results of the research and discussion show that there is an increase in student learning outcomes in social studies learning through the application of problem solving methods. The increase in learning outcomes is marked by an increase in the total value of students' learning completion achievements, namely at the pre-cycle stage it was 23.8%, then in cycle I it increased to 57.1%, and in cycle II it increased further to 85.7%.